Incorporating an intersectional gender approach to improve access to maternal and child health screening services - Margarita Rivera Arrivillaga; Marina Gold; Elizabeth Pellecer Rivera; Jose Guillermo Juárez (BMC, 2024)
Abstract Background In the Americas, the Pan American Health Organization (PAHO) has promoted initiatives that aim at the elimination of mother-to-child transmitted diseases for over two decades. Although Guatemala has assumed the commitment to improve access and coverage of reproductive and perinatal services, the goals have not yet been reached. Often, the implementation of these efforts is hampered by complexities rooted in social, cultural, and environmental intersections. The objective of this work is to share our experience applying gender intersectionality as a methodological and analytical tool in a participatory research project that aims to improve access to maternal and child health screening services. The study shows the novel strategy that incorporates intersectionality contributing to evidence on how it can be applied to strengthen public health efforts around the implementation of the EMTCT Plus (Elimination of mother-to-child transmission of HIV, Syphilis, Hepatitis B, and Chagas disease) framework, in the mostly rural municipality of Comapa, in Guatemala. Methods We applied a participatory methodology, integrating theoretical and methodological frameworks to have an intersectional understanding of health services delivered by both, midwives, and the public health institution, for the prevention, diagnosis, treatment, and follow-up of HIV, Syphilis, Hepatitis B, and Chagas. The data was collected by conducting interviews, focus groups, workshops, and reviewing laboratory databases, guided by five strategies from a cultural appropriateness framework. Results The intersectional analysis shed light on the synergies and gaps of the current efforts and protocols implemented by both the midwives and the Ministry of Health. The services offered for the four diseases were often delivered independently from each other, and a comprehensive educational and communication material strategy was absent. However, our findings will be used to inform consistent, locally relevant, and culturally appropriate educational content for the local population, also following the national policy guidelines. Conclusions Using intersectionality as a method and as an analytical tool allowed us to understand the (1) interrelation of diverse social, cultural, and environmental determinants which influence the delivery of health services, as well as (2) the dynamics between the traditional and institutional health systems. (3) Community engagement and the participation of different stakeholders in a consultative process have been fundamental for the conceptual and methodological tenets of this research. (4) Finally, giving a more prominent role to midwives can strengthen sustainability and cultural appropriateness, which is complementary to the delivery of institutional health services.